Development and disordres in the process of communication of people with the chromosome 13q deletion syndrome - Binkuńska, Ewa (Logopedia Silesiana, 2021)
Chromosome 13q deletion syndrome is a kind of chromosome aberration which belongs to rarely occurring genetic abnormalities. Chromosome 13q deletion results in phenotypic disorders such as malfunctions in the central nervous system, anatomical changes of the body, as well as disorders in large and small motor skills. One of the possible consequences of the problems in motor skills development are speech development disorders, particularly concerning speech production. Other problems may relate to breathing, phonation and articulation. Additionally, on the one hand, some persistent reflexes in the orofacial area can be observed, while, on the other hand, some reflexes are absent. In the case of chromosome 13q deletion, the logopedic therapy contains also swallowing, as well as exercises which aim at improving the muscle tension in the area of face, articulators, neck, shoulders, chest and upper limbs. Disorders in speech production may take form of dysarthria, for example. Whereas, learning to communicate may require to introduce alternative communication – non-verbal communication within language production.